Estimation of Stature from Various Body Parameters in Population of Vidharbha, Maharashtra - Marvel G. Bhosle; Tanu Y. Padole; Malojirao S. Bhosale; Yashwanth Jalagari; Priyavandana Kavalampet; Deepika Bhandari (Brazilian Journal of Forensic Sciences, Medical Law and Bioethics)
In cases of a person found mutilated and dismembered or where a skeleton has parts missing, stature is a crucial parameter for identifying the deceased. This study aims to derive regression equations for numerous body parameters while identifying the most accurate body parameter for measuring stature. Fourteen body parameters from the upper and lower extremities were carefully measured, along with hip size, which had not been included in previous studies. The study involved a population sample of 150 females and 150 males from the Vidarbha region of Maharashtra. The present study demonstrated that upper as well as lower extremities have positive correlation with stature. However, lower extremity had higher correlation with stature as compared to upper extremity. Compared to other body parameters, iliac to foot had lowest Standard Error of the Estimate (SEE) in males (SEE±3.49) and females (SEE±3.38) and highest correlation with stature in males (r2= 0.7) and females (r2=0.63). Thus, Iliac to foot was considered as the best parameter to estimate stature. On the other hand, hip size had highest SEE in males (SEE ±6.99) and females (SEE ±5.46) and very less correlation in males (r2=0.00) and females (r2=0.04). Thus, hip size was considered as worst body parameter to estimate stature in both males and females. Also, regression equations derived in this study could be successfully and reliably used to estimate stature in population of Vidharbha, Maharashtra.